2023
DOI: 10.3390/met13030567
|View full text |Cite
|
Sign up to set email alerts
|

Stress Corrosion Cracking Mechanisms of UNS S32205 Duplex Stainless Steel in Carbonated Solution Induced by Chlorides

Abstract: Herein, the chloride-induced stress corrosion cracking (SCC) mechanisms of UNS S32205 duplex stainless steel (DSS) reinforcing bars in alkaline and carbonated solutions are studied. Electrochemical monitoring and mechanical properties were tested using linear polarization resistance and electrochemical impedance spectroscopy, coupled with the slow strain rate tensile test (SSRT) to evaluate the SCC behavior and unravel the pit-to-crack mechanisms. Pit initiation and crack morphology were identified by fractogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Duplex stainless steel is a resource-saving, high-performance steel product, and its production and application are consistent with the future development of stainless steel [1][2][3][4][5][6][7]. The development of ocean-related resources has always been a research hotspot.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Duplex stainless steel is a resource-saving, high-performance steel product, and its production and application are consistent with the future development of stainless steel [1][2][3][4][5][6][7]. The development of ocean-related resources has always been a research hotspot.…”
Section: Introductionmentioning
confidence: 77%
“…Based on the lateral stiffness theory, the 18 short columns in the tests were taken as objects, and the calculations were conducted with the theoretical Equation (2). The comparison between the theoretical and test values for lateral stiffness is presented in Table 8.…”
Section: Lateral Stiffness Theoretical and Test Value Comparisonmentioning
confidence: 99%
“…UNS S32205 showed major areas of ductile areas, with microvoids and coalescence of dimples attributed to the ductile behavior of the γ-phase (see Figure 3a) [43]. However, when UNS S32205 developed brittle fracture, cracks on the ferrite facets were seen, thus showing that the α-phase is the more SCC-susceptible phase (see Figure 3d) [28,44]. UNS S31653 also developed microvoids and coalescence of dimples for the ductile fracture (see Figure 3b), nevertheless, for the brittle fracture, cracks inside the dimples were the predominant feature, besides the development of cleavage planes (see Figure 3e) [45].…”
Section: Fractographic Studymentioning
confidence: 99%
“…However, a few studies are found on the SCC mechanisms of the steel reinforcement [27][28][29][30]. While it is less studied, SCC of the steel reinforcement causes a sudden brittle fracture, leading to a catastrophic failure without any previous sign of damage.…”
Section: Introductionmentioning
confidence: 99%
“…Tap water contains anions (e.g., Cl − , HCO 3 − , SO 4 2− ) and cations (e.g., Ca 2+ , Mg 2+ ), which play important roles in the corrosion of heating tubes [9][10][11][12]. Cl − ions must adsorb on the metal surface and subsequently cause the breakdown of passive films and the occurrence of pitting corrosion.…”
Section: Introductionmentioning
confidence: 99%